Assessment of clinical variables as predictive markers in the development and progression of colorectal cancer. Issue 1 (1st January 2021) - Rasool, Mahmood; Malik, Arif; Waquar, Sulayman; Ain, Qura Tul; Rasool, Rabia; Asif, Muhammad; Anfinan, Nisreen; Haque, Absarul; Alam, Hina; Ahmed, Sagheer; Hamid Hamdard, Mohammad
ABSTRACT: Colorectal cancer (CRC) is graded as one of the most common cancer. It accounts for the second leading cause of cancer deaths worldwide. The present study intends to investigate the role and importance of different biochemical variables in the development of colorectal cancer. In this cross-sectional study we recruited ninety-one patients diagnosed with colorectal cancer and fifty-three age-sex matched controls from June 2017 to June 2018. Different variables i.e . SOD, GSH, CAT, MDA, TGF, VEGF, TNF, ILs, MMPs, etc., were estimated with the help of their respective methods. Our findings suggest a significant increase in the levels of different inflammatory and stress-related markers. The NFκB, TGF-β, VEGFβ, 8OHdG, IsoP-2α were significantly found to be increased in patients with colon cancer (0.945 ± 0.067 μg/ml, 18.59 ± 1.53 pg/ml, 99.35 ± 4.29 pg/ml, 21.26 ± 1.29 pg/ml, 102.25 ± 4.25 pg/ml) as compared to controls (0.124 ± 0.024 μg/ml, 8.26 ± 0.88 pg/ml, 49.58 ± 2.62 pg/ml, 0.93 ± 0.29 pg/ml, 19.65 ± 3.19 pg/ml). Notably, the levels of different antioxidants were shown to be significantly lower in patients of colon cancer. The present study concluded that excessive oxidative stress and lipid peroxidation result in a decrease in the antioxidative capacity of cells which may influence diverse signaling cascades including NF-KB, which results in DNA modification and gene transcription that ultimately involved in the progression of colon cancer. Graphical Abstract: uf0001